2019
DOI: 10.1016/j.joca.2019.02.800
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing osteoarthritis from T2 maps using deep learning: an analysis of the entire Osteoarthritis Initiative baseline cohort

Abstract: Objective: We aim to study to what extent conventional and deep-learning-based T 2 relaxometry patterns are able to distinguish between knees with and without radiographic osteoarthritis (OA). Methods: T 2 relaxation time maps were analyzed for 4,384 subjects from the baseline Osteoarthritis Initiative (OAI) Dataset. Voxel Based Relaxometry (VBR) was used for automatic quantification and voxelbased analysis of the differences in T 2 between subjects with and without radiographic OA. A Densely Connected Convolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 35 publications
0
51
0
1
Order By: Relevance
“…Our predictive models showed that T tuning the hyperparameter for the tree depths can be performed. 33 In reality, building highly accurate predictive and diagnostic models for OA requires rigorous feature engineering methods 34,35 work which is beyond the scope of this paper. We limited this initial study to the T 2 analysis of average values across compartments, however, previous studies reported that spatial assessment of the knee cartilage relaxation times using laminar and sub-compartmental analyses could lead to better and probably earlier identification of cartilage matrix abnormalities 36,37 Extraction of second-order statistical information or texture analysis 38,39 has been widely used to overcome the limitation of the average-based approaches.…”
Section: T 2 Values and Tkrmentioning
confidence: 99%
See 1 more Smart Citation
“…Our predictive models showed that T tuning the hyperparameter for the tree depths can be performed. 33 In reality, building highly accurate predictive and diagnostic models for OA requires rigorous feature engineering methods 34,35 work which is beyond the scope of this paper. We limited this initial study to the T 2 analysis of average values across compartments, however, previous studies reported that spatial assessment of the knee cartilage relaxation times using laminar and sub-compartmental analyses could lead to better and probably earlier identification of cartilage matrix abnormalities 36,37 Extraction of second-order statistical information or texture analysis 38,39 has been widely used to overcome the limitation of the average-based approaches.…”
Section: T 2 Values and Tkrmentioning
confidence: 99%
“…Voxelbased relaxometry techniques have also been previously proposed 40 ; this technique allows for the investigation of local cartilage composition differences, through voxel-based statistics as statistical parametric mapping, 41 principal component analysis, 42 or deep learning feature extractions. 34 TKR is the most effective intervention for end-stage OA 12 ;…”
Section: T 2 Values and Tkrmentioning
confidence: 99%
“…One pioneer study by Pedoia et al investigated the diagnostic difference of distinguishing knees with and without radiographic OA using conventional and deep learning-based T2 relaxometry measures. 58 In their study, the T2 maps from 4,384 subjects from the baseline OAI data sets were extracted and analyzed. A deep learning method using DenseNet 59 was trained to diagnose OA directly from the T2 maps with a training, validation, and holdout testing set of a 65%-20%-15% split of the entire data sets.…”
Section: Quantitative Imaging For Disease Diagnosismentioning
confidence: 99%
“…Using a hold-out testing group consisting of 83 pelvic radiographs, the machine had an AUC of 0.94 for determining the presence (KL grades 0 and 1) or absence (KL grades 2, 3, and 4) of radiographic OA with a sensitivity and specificity of 95% and 91%, respectively. 50 A recent study by Pedoia et al 51 used a deep-learning method combined with voxel-based relaxometry for the analysis of T 2 relaxation time maps to determine the presence or absence of radiographic knee OA using the interpretation of experienced radiologists as the reference standard. A shallow random forest classifier model trained on handcrafted features consisting of average cartilage T 2 values on different articular surfaces of the knee joint was compared to a DenseNet classification CNN model trained on the raw T 2 data.…”
Section: Estimation Of Pediatric Bone Age On Radiographsmentioning
confidence: 99%